The Unpublished Legends of Virgil - Leland, Charles Godfrey, 1824-1903 (Salt Lake City, UT : Project Gutenberg, 2020)
"The Unpublished Legends of Virgil" by Charles Godfrey Leland is a collection of folkloric tales written in the late 19th century. This work brings together various legends that have accumulated around the famous Roman poet Virgil, reimagining him as both a poet and a magician. The collection is expected to delve into a unique blend of mythology, sorcery, and folkloric traditions, showcasing Virgil's character as a benevolent and humorous figure who assists others with his magical prowess. The opening of the text begins with a preface that sets the stage for Leland's exploration of Virgilian legends. He explains that these tales were primarily gathered from local sources such as witches and fortune-tellers, emphasizing their rich connections to Etrusco-Roman folklore. Leland notes the intriguing aspects of Virgil's portrayal; he emerges not just as a significant literary figure but also as an emblem of everyday magic and wisdom. The initial tales include the mythological origins of Virgil's birth, stories of transformations, heroic quests, and interactions with divine and mystical entities, foreshadowing a world where magic intertwines seamlessly with the lives of mortals. (This is an automatically generated summary.)
Release date is 2020-06-07
Transcribed from the 1899 Elliot Stock edition by David Price
Keywords: Folklore -- Italy; Virgil -- Legends; Poets -- Legends; Legends -- Rome